2015
DOI: 10.1007/s13277-015-3678-6
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of annexin A2 expression predicates advanced clinicopathological features and poor prognosis in hepatocellular carcinoma

Abstract: Hepatic annexin A2 (ANXA2) orchestrates multiple biologic processes and clinical symptoms and plays a key role in development, metastasis, and drug resistance of lethal hepatocellular carcinoma (HCC). However, the prognostic significance of ANXA2 for HCC has not been elucidated up to now. In this study, ANXA2 was frequently found to be up-regulated in HCC tissues compared with benign liver disease (BLD) tissues, which was consistent with the results in serum samples and tissue specimens of patients with HCC. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…These results indicate that Annexin 2 may be an independent prognostic factor for hepatocellular carcinoma (20). Previous studies have demonstrated that the expression of Annexin A2 is significantly associated with metastasis and poor survival in nasopharyngeal and endometrial carcinoma, bladder cancer and serous ovarian cancer (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 54%
“…These results indicate that Annexin 2 may be an independent prognostic factor for hepatocellular carcinoma (20). Previous studies have demonstrated that the expression of Annexin A2 is significantly associated with metastasis and poor survival in nasopharyngeal and endometrial carcinoma, bladder cancer and serous ovarian cancer (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 54%
“…Several studies have demonstrated an up‐regulation of ANXA2 in human and experimental hepatocarcinogenesis, and have suggested that an elevated level of ANXA2 may be an independent serological marker for the early diagnosis of HCC . Furthermore, ANXA2 expression is significantly correlated with tumor stage and closely associated with overall survival of HCC patients …”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was performed as described before [24]. Student's t -test was used to compare CACNA1B (Ca v 2.2) mRNA and protein expression between tumorous and nontumorous tissue samples.…”
Section: Methodsmentioning
confidence: 99%